Optimization studies on catalytic pyrolysis of empty fruit bunch (EFB) using L9 Taguchi Orthogonal Array - Doraiselvan, K. (Italian Association of Chemical Engineering - AIDIC, 2015)
In this investigation, catalytic pyrolysis of empty fruit bunch (EFB) was studied and optimized in terms of bio-oil and char yields by using Taguchi L9 Orthogonal Array method. The effects of pyrolysis temperatures, catalyst loadings and particle sizes on the product yields were investigated and discussed in this paper. The catalytic pyrolysis is performed in a semi-batch reactor which is externally heated by an electrical vertical split tube furnace. Under the nitrogen flow rates of 60 ml/min, 80 mL/min and 100 mL/min, 15 g of EFB biomass with the particle sizes of 100 Î¼m, 250 Î¼m, 500 Î¼m were thermally decomposed at three pyrolysis temperatures of 573 K, 673 K and 773 K, along with Zeolite HZSM-5 catalyst loadings of 1 wt, 5 wt and 12 wt. From the product analysis, a maximum liquid bio-oil yield of 64.4 wt were obtained at catalyst loading of 1.5 wt., reaction temperature of 773 K, nitrogen flow rate of 100 mL/min, and particle size of 250 Î¼m. Meanwhile, at catalyst loading of 3.25 wt., reaction temperature of 773 K, nitrogen flow rate of 60 mL/min and particle size of 250 Î¼m, the bio char yield formed was as low as 18.6 wt. which could be mainly attributed to secondary cracking of char residue. Copyright Â© 2015, AIDIC Servizi S.r.l.,.